The Role of the si-Face Tyrosine of a Homodimeric Ferredoxin-NADP+ Oxidoreductase from Bacillus subtilis during Complex Formation and Redox Equivalent Transfer with NADP+/H and Ferredoxin - Daisuke Seo (MDPI AG, 2023)
In the crystal structure of ferredoxin-NADP+ oxidoreductase from Bacillus subtilis (BsFNR), Tyr50 stacks on the si-face of the isoalloxazine ring portion of the FAD prosthetic group. This configuration is highly conserved among the homodimeric ferredoxin-NAD(P)+ oxidoreductases (FNR) from Gram-positive bacteria and photosynthetic bacteria. In this report, pre-steady state reactions of Tyr50 variants with NADP+/NADPH and ferredoxin from B. subtilis (BsFd) were examined with stopped-flow spectrophotometry to assess the effects of the mutation on the formation of FNR-substrate complexes and following redox equivalent transfer. Mixing oxidized BsFNRs with NADPH resulted in a rapid complex formation followed by a rate-limiting hydride transfer. The substitution substantially modulated the intensity of the charge transfer absorption band and decreased the observed hydride transfer rates compared to the wild type. Reduction of the Y50W mutant by NADPH proceeded in a monophasic manner, while the Y50G and Y50S mutants did in biphasic phases. The reduced Tyr50 mutants hardly promoted the reduction of NADP+. Mixing oxidized BsFNRs with reduced BsFd resulted in the reduction of the FNRs. The observed FNR reduction rates of the three variants were comparable, but in the Y50G and Y50S mutants, the amount of the reduced FNR at the rapid phase was decreased, and a slow FNR reduction phase was observed. The obtained results suggest that the replacements of Tyr50 with Gly and Ser permitted the conformational change in the reduced form, which induced an asymmetric kinetic behavior between the protomers of the homodimeric BsFNR.